Pengasuhan Anak dalam Perspektif Mubadalah - Indar Wahyuni; Nurul Ma’rifah (AL-BURHAN, 2022)
The purpose of marriage is to form a sakinah mawaddah warahmah family. The ideal of forming a happy and prosperous family is impossible if the patriarchal culture is still firmly attached to men's thinking. where a man has a very dominant role in controlling life, while a woman (wife) is only used as a complement, or in Javanese terms commonly referred to as konco wingking (back friend) which means women only have a position as followers. The family is the first place for children when born from it will learn many things in daily life, so that parenting will affect whether it only involves the role of the father or both are equally active so that the quality of the child's cognitive, affective and psychomotor will develop well. The purpose of this study is to describe how parenting is in a mublah perspective. Based on the description of the background above, there is a problem formulation on how to raise children in the Mublah Perspective. This research method uses a qualitative approach with the type of research. Library Research. The research carried out is reading various literature studies on parenting both in Islam and by law as well as reading literature on Mublah's perspective in the Qiro'ah Mublah book. Data collection is done through the Documentation method. This research was conducted by means of triangulation from book sources. The analysis process is carried out simultaneously with data collection through several stages, namely data reduction, data presentation, and conclusions. The results showed that: Parenting in Mub's Perspective is the existence of mutual cooperation, mutual cooperation between fathers and mothers in raising children, being a shared responsibility between fathers and mothers, This means that there is no inequality of responsibility in raising children. Children born male or female both have the right to be protected, cared for and educated. Children who develop in a harmonious family and gender justice affect their personality, so that the role of the family, both father and mother, has an important role and is a key and main factor for children's success.